Dor aguda e relação de gênero : diferentes percepções em homens e mulheres - Lira, Margaret Olinda de Souza Carvalho e (2013)
The investigation had as objective, analysing the pain perception differences between men and women. It explores different authors' comprehensions about the pain in a gender perspective. It presents results referring to admitted clients on emergency service, medical and surgery clinics of a public hospital in the city of Petrolina - PE. The data quatitative analysis found pain perception differences between the 12 emotional components investigated. It's pretended to provide elements that contribute to the enlargement of the knowledge about the theme as also to the implantation of mensuration scales of pain.